Effect of clean and healthy living behavior (chlb) training on students’ knowledge in marqiz daarul quran wassunnah islamic boarding school, Riau: a quasi-experimental study - Winarto, Winarto; Firdaus, Firdaus; Darmawi, Darmawi; Nurkasanah, Siti (Journal of Community Empowerment for Health, 2026)
Introduction: Islamic boarding schools (pesantren) face sanitation and behavioral challenges that increase the risk of preventable infectious diseases. Clean and Healthy Living Behavior (CHLB) programs have been promoted nationally; however, limited evidence evaluates the effectiveness of CHLB training on student knowledge in Marqiz Daarul Quran Wassunnah Islamic Boarding School in Kampar, Riau. Therefore, this study aims to evaluate the effect of CHLB training on students’ knowledge at Marqiz Daarul Quran Wassunnah Islamic Boarding School using a one-group pretest–posttest quasi-experimental approach.Methods: This quasi-experimental study involved 62 male students aged 6.5–50 years from Marqiz Daarul Quran Wassunnah Islamic Boarding School in Kampar, Riau. Knowledge was assessed using a validated 15-item questionnaire before and after a 120-minute structured training session. A paired t-test with 95% confidence level was used to compare mean pre- and post-test scores (α = 0.05).Results: Knowledge improved following training, as indicated by a decrease in the mean number of incorrect responses from 3.46 (pre-test) to 1.77 (post-test), with a statistically significant difference (p = 0.0429). However, increased post-test score variability suggested differing levels of understanding among participants.Conclusion: CHLB training significantly improved students' knowledge, though unequal learning gains suggest that a single training session may be insufficient for comprehensive understanding. Integrating recurring training, structured reinforcement, and Poskestren involvement may support long-term behavior change and sustain hygiene practices.